(x+1)(x+1)(x+3i)(x-3i)=0

Simple and best practice solution for (x+1)(x+1)(x+3i)(x-3i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+1)(x+1)(x+3i)(x-3i)=0 equation:


Simplifying
(x + 1)(x + 1)(x + 3i)(x + -3i) = 0

Reorder the terms:
(1 + x)(x + 1)(x + 3i)(x + -3i) = 0

Reorder the terms:
(1 + x)(1 + x)(x + 3i)(x + -3i) = 0

Reorder the terms:
(1 + x)(1 + x)(3i + x)(x + -3i) = 0

Reorder the terms:
(1 + x)(1 + x)(3i + x)(-3i + x) = 0

Multiply (1 + x) * (1 + x)
(1(1 + x) + x(1 + x))(3i + x)(-3i + x) = 0
((1 * 1 + x * 1) + x(1 + x))(3i + x)(-3i + x) = 0
((1 + 1x) + x(1 + x))(3i + x)(-3i + x) = 0
(1 + 1x + (1 * x + x * x))(3i + x)(-3i + x) = 0
(1 + 1x + (1x + x2))(3i + x)(-3i + x) = 0

Combine like terms: 1x + 1x = 2x
(1 + 2x + x2)(3i + x)(-3i + x) = 0

Multiply (1 + 2x + x2) * (3i + x)
(1(3i + x) + 2x * (3i + x) + x2(3i + x))(-3i + x) = 0
((3i * 1 + x * 1) + 2x * (3i + x) + x2(3i + x))(-3i + x) = 0
((3i + 1x) + 2x * (3i + x) + x2(3i + x))(-3i + x) = 0
(3i + 1x + (3i * 2x + x * 2x) + x2(3i + x))(-3i + x) = 0
(3i + 1x + (6ix + 2x2) + x2(3i + x))(-3i + x) = 0
(3i + 1x + 6ix + 2x2 + (3i * x2 + x * x2))(-3i + x) = 0
(3i + 1x + 6ix + 2x2 + (3ix2 + x3))(-3i + x) = 0

Reorder the terms:
(3i + 6ix + 3ix2 + 1x + 2x2 + x3)(-3i + x) = 0
(3i + 6ix + 3ix2 + 1x + 2x2 + x3)(-3i + x) = 0

Multiply (3i + 6ix + 3ix2 + 1x + 2x2 + x3) * (-3i + x)
(3i * (-3i + x) + 6ix * (-3i + x) + 3ix2 * (-3i + x) + 1x * (-3i + x) + 2x2 * (-3i + x) + x3(-3i + x)) = 0
((-3i * 3i + x * 3i) + 6ix * (-3i + x) + 3ix2 * (-3i + x) + 1x * (-3i + x) + 2x2 * (-3i + x) + x3(-3i + x)) = 0

Reorder the terms:
((3ix + -9i2) + 6ix * (-3i + x) + 3ix2 * (-3i + x) + 1x * (-3i + x) + 2x2 * (-3i + x) + x3(-3i + x)) = 0
((3ix + -9i2) + 6ix * (-3i + x) + 3ix2 * (-3i + x) + 1x * (-3i + x) + 2x2 * (-3i + x) + x3(-3i + x)) = 0
(3ix + -9i2 + (-3i * 6ix + x * 6ix) + 3ix2 * (-3i + x) + 1x * (-3i + x) + 2x2 * (-3i + x) + x3(-3i + x)) = 0

Reorder the terms:
(3ix + -9i2 + (6ix2 + -18i2x) + 3ix2 * (-3i + x) + 1x * (-3i + x) + 2x2 * (-3i + x) + x3(-3i + x)) = 0
(3ix + -9i2 + (6ix2 + -18i2x) + 3ix2 * (-3i + x) + 1x * (-3i + x) + 2x2 * (-3i + x) + x3(-3i + x)) = 0
(3ix + -9i2 + 6ix2 + -18i2x + (-3i * 3ix2 + x * 3ix2) + 1x * (-3i + x) + 2x2 * (-3i + x) + x3(-3i + x)) = 0

Reorder the terms:
(3ix + -9i2 + 6ix2 + -18i2x + (3ix3 + -9i2x2) + 1x * (-3i + x) + 2x2 * (-3i + x) + x3(-3i + x)) = 0
(3ix + -9i2 + 6ix2 + -18i2x + (3ix3 + -9i2x2) + 1x * (-3i + x) + 2x2 * (-3i + x) + x3(-3i + x)) = 0
(3ix + -9i2 + 6ix2 + -18i2x + 3ix3 + -9i2x2 + (-3i * 1x + x * 1x) + 2x2 * (-3i + x) + x3(-3i + x)) = 0
(3ix + -9i2 + 6ix2 + -18i2x + 3ix3 + -9i2x2 + (-3ix + 1x2) + 2x2 * (-3i + x) + x3(-3i + x)) = 0
(3ix + -9i2 + 6ix2 + -18i2x + 3ix3 + -9i2x2 + -3ix + 1x2 + (-3i * 2x2 + x * 2x2) + x3(-3i + x)) = 0
(3ix + -9i2 + 6ix2 + -18i2x + 3ix3 + -9i2x2 + -3ix + 1x2 + (-6ix2 + 2x3) + x3(-3i + x)) = 0
(3ix + -9i2 + 6ix2 + -18i2x + 3ix3 + -9i2x2 + -3ix + 1x2 + -6ix2 + 2x3 + (-3i * x3 + x * x3)) = 0
(3ix + -9i2 + 6ix2 + -18i2x + 3ix3 + -9i2x2 + -3ix + 1x2 + -6ix2 + 2x3 + (-3ix3 + x4)) = 0

Reorder the terms:
(3ix + -3ix + 6ix2 + -6ix2 + 3ix3 + -3ix3 + -9i2 + -18i2x + -9i2x2 + 1x2 + 2x3 + x4) = 0

Combine like terms: 3ix + -3ix = 0
(0 + 6ix2 + -6ix2 + 3ix3 + -3ix3 + -9i2 + -18i2x + -9i2x2 + 1x2 + 2x3 + x4) = 0
(6ix2 + -6ix2 + 3ix3 + -3ix3 + -9i2 + -18i2x + -9i2x2 + 1x2 + 2x3 + x4) = 0

Combine like terms: 6ix2 + -6ix2 = 0
(0 + 3ix3 + -3ix3 + -9i2 + -18i2x + -9i2x2 + 1x2 + 2x3 + x4) = 0
(3ix3 + -3ix3 + -9i2 + -18i2x + -9i2x2 + 1x2 + 2x3 + x4) = 0

Combine like terms: 3ix3 + -3ix3 = 0
(0 + -9i2 + -18i2x + -9i2x2 + 1x2 + 2x3 + x4) = 0
(-9i2 + -18i2x + -9i2x2 + 1x2 + 2x3 + x4) = 0

Solving
-9i2 + -18i2x + -9i2x2 + 1x2 + 2x3 + x4 = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-1x2' to each side of the equation.
-9i2 + -18i2x + -9i2x2 + 1x2 + 2x3 + -1x2 + x4 = 0 + -1x2

Reorder the terms:
-9i2 + -18i2x + -9i2x2 + 1x2 + -1x2 + 2x3 + x4 = 0 + -1x2

Combine like terms: 1x2 + -1x2 = 0
-9i2 + -18i2x + -9i2x2 + 0 + 2x3 + x4 = 0 + -1x2
-9i2 + -18i2x + -9i2x2 + 2x3 + x4 = 0 + -1x2
Remove the zero:
-9i2 + -18i2x + -9i2x2 + 2x3 + x4 = -1x2

Add '-2x3' to each side of the equation.
-9i2 + -18i2x + -9i2x2 + 2x3 + -2x3 + x4 = -1x2 + -2x3

Combine like terms: 2x3 + -2x3 = 0
-9i2 + -18i2x + -9i2x2 + 0 + x4 = -1x2 + -2x3
-9i2 + -18i2x + -9i2x2 + x4 = -1x2 + -2x3

Add '-1x4' to each side of the equation.
-9i2 + -18i2x + -9i2x2 + x4 + -1x4 = -1x2 + -2x3 + -1x4

Combine like terms: x4 + -1x4 = 0
-9i2 + -18i2x + -9i2x2 + 0 = -1x2 + -2x3 + -1x4
-9i2 + -18i2x + -9i2x2 = -1x2 + -2x3 + -1x4

Reorder the terms:
-9i2 + -18i2x + -9i2x2 + x2 + 2x3 + x4 = -1x2 + x2 + -2x3 + 2x3 + -1x4 + x4

Combine like terms: -1x2 + x2 = 0
-9i2 + -18i2x + -9i2x2 + x2 + 2x3 + x4 = 0 + -2x3 + 2x3 + -1x4 + x4
-9i2 + -18i2x + -9i2x2 + x2 + 2x3 + x4 = -2x3 + 2x3 + -1x4 + x4

Combine like terms: -2x3 + 2x3 = 0
-9i2 + -18i2x + -9i2x2 + x2 + 2x3 + x4 = 0 + -1x4 + x4
-9i2 + -18i2x + -9i2x2 + x2 + 2x3 + x4 = -1x4 + x4

Combine like terms: -1x4 + x4 = 0
-9i2 + -18i2x + -9i2x2 + x2 + 2x3 + x4 = 0

The solution to this equation could not be determined.

See similar equations:

| 7x-3=7(x+8) | | 3y^2+18=90 | | 3/4x-1=1/2x | | 100-(2y+12)(5y+6)=4-10y | | s=l*(1-R) | | X^3=2.9 | | 6*(x+1)=2*(5+3x) | | 9z+2-4=4+4z-6 | | 5(x+3)=10-2(x+2) | | 2(120-5x/10) | | -30-6n=-10-2(3n+10) | | 1.2=0.1x | | 3x+2(x-2)+9=0 | | x-(.3x)=28 | | (.3x)-x=28 | | 10-k=k-6 | | 0.41x+x=117 | | 3*(x+1)=2*(x+11) | | x^2-13x-23=-4x-1 | | .3x-x=28 | | -3(-5v-4v-4y+3)= | | (4x^(2/7))(3x^(1/3)) | | 9*(z-3)=12z | | 5x-105=-4x+30 | | -3x-7+2x+5x-11x= | | 5x-x-7=-4x+2 | | (3x+1)+4i=-2+(3y-2)i | | 0.5x^2-3x+4=0 | | 10x+64+5x=65x-36 | | -3-2(6)= | | -2(x+6)+3x= | | 3x-10=5x+45 |

Equations solver categories